The Problem Body : Projecting Disability in Film - Markotić, Nicole; Chivers, Sally, 1972- (Book collections on Project MUSE., 2010)
"To call into question why certain bodies invite the label "problem" more frequently than other bodies, the contributors draw on scholarship from feminist, race, queer, cultural, disability, and film studies arenas. In Chivers and Markotic's introduction, they draw on disability theory and a range of cinematic examples to explain the term "problem body" in relation to its "projection." In explorations of film noir, illness narratives, classical Hollywood film, Korean film, and European film, the essays reveal the "problem body" as a multiplication of lived circumstances constructed both physically and socially"--Book jacket.